Standard Operating Crime Investigation Traffic Accidents - M Farid Amirullah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
History Traffic in Indonesia can not be separated from the development of the world Automotive technology, which originated from the discovery of the engine with petroleum fuels. In the days of the Dutch East Indies government then ruled Indonesia started bringing vehicles wheel 4 and wheel 2 to Indonesia, causing traffic activity. And when the car and motorcycle multiply causing many problems - the problems of traffic, such as traffic violations and accidents. Given the above, of course of police duties particularly Traffic Police Unit increasingly severe, in the sense of Traffic Police Unit should continue to maintain and improve the technical capacity of the police in order to deal with problems like traffic violations and traffic accidents, in addition to the Police Unit Then Trails should be able to provide a breakthrough in order to increase awareness to the public about the correct procedures and safe traffic and police action to reduce the number of traffic accidents on the road. For that to improve the professionalism and quality of work performed is necessary to standardize the work that will be used as working guidelines called the Standard Operation Procedure (SOP)Keywords: Standard Operating Procedure; Investigation; Traffice Accident.